Who do you blame in local finance? An analysis of municipal financing in Italy - Massimo Bordignon; Veronica Grembi; Santino Piazza (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2015)
In a political agency model, we study the effect of introducing a less transparent tax tool for the financing of local governments. We show that lower quality politicians would use more the less transparent tax tool to enhance their probability of re-election. This prediction is tested by studying a reform that in 1999 allowed Italian municipalities to partially substitute a more accountable source of tax revenue (the property tax) with a less transparent one (a surcharge on the personal income tax of residents). Using a Difference in Difference approach, we show that in line with theory, Mayors at their first term in power adopted a higher surcharge on the personal income tax and reduced the property tax rate significantly more than Mayors in their final term..
Keywords: H71; H77; D78; 330; Fiscal federalism; Tax transparency; Agency Model; Property tax